Sustainable Tourism Development Strategy on Sumba Island: Utilising Cultural and Natural Resources for Local Economic Resilience - Wisnawa, I Made Bayu (Language Assistance, 2024)
This study aims to explore sustainable tourism development strategies on Sumba Island, focusing on community involvement, infrastructure improvement, and natural resource management to strengthen the local economy while preserving the environment and culture. A qualitative approach utilizing case study analysis, in-depth interviews with local stakeholders, and a literature review was employed to examine the theories of creative economy and ecotourism management. Key findings reveal that community engagement and training are crucial elements for sustainable tourism development. Strategic natural resource management and infrastructure improvement can enhance tourist attraction and economic resilience. The study contributes original insights by integrating an ecosystem-based approach into tourism strategies on Sumba. Limitations of the research include the lack of quantitative data and accessibility challenges to remote locations on the island. The implications of the study emphasize the importance of further collaboration among the government, local communities, and the private sector. This research also recommends the development of policies and investments that support the local ecosystem, as well as ongoing training programs to improve managerial and service skills in the tourism sector. Additionally, the study suggests further research on the impact of climate change on Sumba’s tourism industry and the role of technology in supporting sustainable tourism initiatives.